2013
DOI: 10.1177/156482651303400201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Breastfeeding on Weight Loss and Recovery of Pregestational Weight in Adolescent and Adult Mothers

Abstract: EBF in adolescent and adult mothers influences postpartum weight loss and provides adequate infant growth in accordance with the WHO 2006 standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 26 publications
0
25
0
9
Order By: Relevance
“…We updated the systematic review by Neville et al. by including 5 additional studies (Table ) . In the review by Neville et al., the majority of identified studies reported little or no association between breastfeeding and weight change.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We updated the systematic review by Neville et al. by including 5 additional studies (Table ) . In the review by Neville et al., the majority of identified studies reported little or no association between breastfeeding and weight change.…”
Section: Resultsmentioning
confidence: 99%
“…No new studies were found subsequent to the systemic review conducted by Dias and Figueiredo in 2015 (32). (Table 5) (191)(192)(193)(194)(195). In the review by Neville et al, the majority of identified studies reported little or no association between breastfeeding and weight change.…”
Section: Postpartum Depressionmentioning
confidence: 99%
“…In contrast to the example of breastfeeding above, age is not found to be associated with postpartum weight loss and therefore may not need to be considered in this particular applicability assessment [51]. The absence of focus in the criteria, with no accompanying guidance, encourages data-driven assessments of generalisability.…”
Section: Resultsmentioning
confidence: 99%
“…Encouraging breastfeeding is important to health of mothers and infants for many reasons. In the context of concerns about postpartum weight retained from pregnancy, exclusive breastfeeding is important for its contribution to postpartum weight loss (Samano et al., ).…”
Section: Discussionmentioning
confidence: 99%